Mechanism of graphene oxide as a growth template for complete reduced graphene oxide coverage on SiO2 substrate - Nimmo, Myra A. (2013)
Reduced Graphene Oxide (rGO) has the distinct advantage of an aqueous and industrial-scalable production route. However large deviation in the electrical resistivity of fabricated rGO devices, caused by inhomogeneous coverage of rGO on the substrate, prevents its practical application in electronic devices. This critical problem could be solved by using an ethanol chemical vapour deposition (CVD) treatment on the graphene oxide (GO). With the treatment, not only GO was reduced to rGO, rGO new growths preferentially grow outwards from the edges of the existing GO template and enlarge in size until rGO completely covered the substrate. The growth sequence was presented and our results indicate that the growth support the free radical condensate growth mechanism. After the ethanol CVD treatment, the standard deviation in electrical resistivity decreased significantly by 99.95% (1.60E+06 to 7.72E+02 Ω/square) in comparison to hydrazine-reduced rGO substrates. As no carbon signatures on the substrate were observed if no template was used; this work indicate that GO could act as template for subsequent formation of rGO.